Bisphenol A affects placental layers morphology and angiogenesis during early pregnancy phase in mice. Issue 11 (9th June 2015) - Tait, Sabrina; Tassinari, Roberta; Maranghi, Francesca; Mantovani, Alberto
Abstract Bisphenol A (BPA) is a widespread endocrine disrupter mainly used in food contact plastics. Much evidence supports the adverse effects of BPA, particularly on susceptible groups such as pregnant women. The present study considered placental development – relevant for pregnancy outcomes and fetal nutrition/programming – as a potential target of BPA. Pregnant CD‐1 mice were administered per os with vehicle, 0.5 (BPA05) or 50 mg kg−1 (BPA50) body weight day−1 of BPA, from gestational day (GD) 1 to GD11. At GD12, BPA50 induced significant degeneration and necrosis of giant cells, increased vacuolization in the junctional zone in the absence of glycogen accumulation and reduction of the spongiotrophoblast layer. In addition, BPA05 induced glycogen depletion as well as significant nuclear accumulation of β‐catenin in trophoblasts of labyrinthine and spongiotrophoblast layers, supporting the activation of the Wnt/β‐catenin pathway. Transcriptomic analysis indicated that BPA05 promoted and BPA50 inhibited blood vessel development and branching; morphologically, maternal vessels were narrower in BPA05 placentas, whereas embryonic and maternal vessels were irregularly dilated in the labyrinth of BPA50 placentas. Quantitative polymerase chain reaction evidenced an estrogen receptor β induction by BPA50, which did not correspond to downstream genes activation; indeed, the transcription factor binding sites analysis supported the AhR/Arnt complex as regulator of BPA50‐modulated genes. Conversely, Creb appeared as the main transcription factor regulating BPA05‐modulated genes. Embryonic structures (head, forelimb) showed divergent perturbations upon BPA05 or BPA50 exposure, potentially related to unbalanced embryonic nutrition and/or to modulation of genes involved in embryo development. Our findings support placenta as an important target of BPA, even at environmentally relevant dose levels. Copyright © 2015 John Wiley & Sons, Ltd.